THE INFLUENCE OF ACUPRESSURE THERAPY AGAINST BLOOD GLUCOSE LEVELS IN PATIENTS OF DIABETES MELLITUS TYPE 2 IN THE PROLANIS PROGRAM (A STUDY ON HEALTH IN AMBALAWI) - mustamin, musmuliadin (Warmadewa University, 2018)
Acupressure lowers the blood glucose level through a massage at the point of the meridian, which can trigger the calming and uplifting response in the body, having a positive effect on emotions, and causing relaxation and normalizing the body functions. However, the great influence of acupressure in the Prolanis Program has not been seen. This study aims to analyze the effect of acupressure therapy against blood glucose levels in patients of diabetes mellitus (DM) type 2, who joined a program of chronic diseases management called Prolanis Program. With quasi-experiment research design, the study was conducted at the Clinic of Ambalawi, Bima District-Indonesia. As many as 34 patients with DM type 2 who have joined the Prolanis Program were selected as participants in this study, using a purposive sampling method. These participants were divided into two groups: experiment group and control group. Acupressure therapy was given 3 times during 3 weeks. Each group was measured for blood glucose levels on day 6, day 12, and day 18. The data were analyzed using t-test (p= 0.05). Giving therapy for three weeks to people with diabetes mellitus type 2 has a positive effect on lowering their blood sugar levels. Acupressure therapy and Prolanis Program for 3 weeks effecttively lowered the blood glucose levels in patients of type 2 of DM. Acupressure therapy has a more significant effect with p value < 0.005. There are significant differences between the experiment group and the control group by p value (p = 0.00).